Transcriptome analysis of muskmelon (Cucumis melo) for moisture stress tolerance - SUPRIYA, P; BHAT, K V (The Indian Journal of Agricultural Sciences, 2022)
Transcriptome is the whole set of RNA molecules transcribed in a cell at a particular time under particular environmental conditions. Assessing the transcriptome and estimating the degree of expression of all genes under different conditions is a crucial step in understanding the dynamic processes that take place during development. In the present study, genes that play a major role in moisture stress were identified using high-throughput transcriptome sequencing analysis. High quality assembled transcripts of Cucumis melo var. agrestis control and stress samples were compared using BlastX with the protein databases available in the public domain. Gene Ontology (GO) analysis revealed that a total of 6263 and 6430 transcripts were assigned at least one GO term from control and stress samples, respectively. Changes of expression level in these transcripts for moisture stress tolerance were detected using RNA-seq mapping. Among stress responsive genes, a total of 122 genes were commonly expressed in both control and stress samples and 72 genes were highly upregulated in stress sample when compared to control sample.